ENHANCING MANAGERIAL PERFORMANCE THROUGH HR COMPETENCIES IN COOPERATIVES - Rasulong, Ismail (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2025)
This study examines the impact of HR competencies (communication, teamwork, leadership, and analytical decision-making) on managerial performance in cooperative organizations. Using a quantitative approach, data were collected from 65 cooperative managers in Barru Regency through structured questionnaires. Multiple linear regression analysis was applied to evaluate the relationships between HR competencies and managerial performance. The findings reveal that analytical decision-making and teamwork are the most significant predictors of performance, highlighting their critical role in fostering operational efficiency and achieving organizational objectives. Communication and leadership, while positively correlated with performance, function as foundational enablers supporting teamwork and decision-making. The study contributes to the literature by emphasizing the interplay between HR competencies and cooperative governance, offering practical recommendations for enhancing managerial effectiveness through targeted training and development programs. These findings underscore the importance of adopting a comprehensive competency framework to optimize organizational outcomes and ensure sustainability. Further research is recommended to explore the contextual factors influencing the variability of HR competencies across different organizational settings.